Evaluation of a Policy for the Distribution of Islamic Boarding School Grant Funds in Banten - Giri, Ujang; Mulyawan, Rahman; Rusli, Budiman; Sumaryana, Asep (KnE Social Sciences, 2022)
Banten Province has eight regional autonomous areas consisting of four cities and four regencies, namely Cilegon City, Serang City, Tangerang City, South Tangerang City, Lebak Regency, Pandeglang Regency, Serang Regency, and Tangerang Regency. There are many Islamic boarding schools in Banten, which is often referred to as the city of santri in the land of champions. Banten Province distributes social assistance for Islamic boarding schools, through the regulation of the Governor of Banten number 10 of 2019 concerning guidelines for the provision of grants and social assistance sourced from the regional revenue and expenditure budget of the Banten Province. Based on the data collected in this study, there were 3,703 Islamic boarding schools in Banten Province in 2020. However, 918 Islamic boarding schools had administrative problems, including those that did not have legal status, an operational permit, or a deed of establishment from the Islamic Boarding School Foundation. Keywords: policy evaluation, distribution grant fund, Islamic boarding school